Postoperative pain in root canal treatment with ultrasonic versus conventional irrigation: a systematic review and meta-analysis of randomized controlled trials - Chalub, Lucas Orbolato [UNESP]; Nunes, Gabriel Pereira [UNESP]; Ferrisse, Túlio Morandin [UNESP]; Strazzi-Sahyon, Henrico Badaoui [UNESP]; Santos, Paulo Henrique dos [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Araújo, Gustavo Sivieri de [UNESP] (Springer Nature, 2022)
Objective: The objective of this systematic review and meta-analysis (SRM) was to answer the question whether the use of ultrasonic irrigation (UI) results in less postoperative pain (PP) compared to conventional irrigation (CI). Methods: A literature search was performed within the main scientific databases carried out until May 2021. The eligibility criteria were randomized clinical trials (RCTs). Meta-analysis was conducted using R software with the “META” package, the mean difference (MD) measure of effect was calculated, and the fixed effect model was applied with a 95% confidence interval (CI). The Cochrane collaboration scale was used to assess risk of bias and the GRADE tool to assess the quality of evidence. Results: Six RCTs were included for systematic review and four for meta-analysis. UI resulted in less PP in 3 of 5 periods, at 6 h (MD − 1.40 [CI − 2.38 to − 0.42] p = 0.0052), 24 h (MD − 0.73 [CI − 1.07 to − 0.39] p = 0.0001), and 48 h (MD − 0.36 [CI − 0.59 to − 0.13] p = 0.022). However, PP showed no significant differences between the groups at 72 h and 7 days (p > 0.05). A low risk of bias was observed for most domains, except allocation that was considered unclear. The certainty of evidence was classified as moderate (24 h, 48 h, and 7 days) and low (6 and 72 h). Conclusion: Within the limitations of this SRM, UI presented less occurrence of PP than CI. Further randomized clinical trials are needed to corroborate these findings. Clinical relevance. UI should be used by clinicians as it reduces postoperative pain in patients undergoing endodontic treatment.
Keywords: Conventional irrigation; Endodontic treatment; Meta-analysis; Postoperative pain; Systematic review; Ultrasonic irrigation